2020
DOI: 10.1186/s13643-020-01472-w
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and adverse events of topical and allergen immunotherapy for atopic dermatitis: a systematic review and network meta-analysis protocol

Abstract: Background Atopic dermatitis (AD) is an inflammatory chronic condition that affects the skin of children and adults and has an important impact on the quality of life. Treatments for AD are based on environmental controls, topical and systemic therapies, and allergen-specific immunotherapy (AIT). However, it remains unclear the effectiveness and adverse events of AIT and all conventional topical treatments compared with placebo and each other for AD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Systemic reactions affecting the entire body can range from anaphylaxis to asthma or urticaria and are generally uncommon in both methods, regardless of SCIT or SLIT [97][98][99]. Similar results regarding the adverse effects of AIT on AD have been noted [100].…”
Section: Attributes Of Aitmentioning
confidence: 55%
“…Systemic reactions affecting the entire body can range from anaphylaxis to asthma or urticaria and are generally uncommon in both methods, regardless of SCIT or SLIT [97][98][99]. Similar results regarding the adverse effects of AIT on AD have been noted [100].…”
Section: Attributes Of Aitmentioning
confidence: 55%
“…Cluster and factor analysis are the two most common methods. Of the 37 BS papers, a manual inspection found that only eight 21 , 33 , 34 , 35 , 36 , 37 , 38 , 39 specifically study AD. Of these eight, half 33 , 34 , 35 , 36 used random‐effects Bayesian network meta‐analysis to compare treatments for AD, and one 21 uses a Bayesian mechanistic machine learning model to predict next‐day AD severity for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster and factor analysis are the two most common methods. Of the 37 BS papers, a manual inspection found that only eight 21,[33][34][35][36][37][38][39] specifically study AD. Of these eight, half [33][34][35][36] used random-effects Bayesian network meta-analysis to compare treatments for AD, and one 21 uses a Bayesian mechanistic machine learning model to predict next-day AD severity for individual patients.…”
Section: Analytical Methods and The Use Of Ad Or Eczema Termsmentioning
confidence: 99%